Wage subsidies, job-displacement and Swedish firms: A comparison between policy systems - Stefano Lombardi; Oskar Nordström Skans; Johan Vikström (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2018)
This paper studies how New Start Jobs (Nystartsjobb) and Employment Subsidies Anställningsstöd) affect Swedish firms. We study effects on the number of employees, firm performance and other firm level outcomes. We use Swedish administrative data from the period 1998-2008. One result is that treated firms substantially outperform other recruiting firms after hiring through subsidies, both in terms of the number of employees and in terms of various production measures, despite having identical pre-match trajectories. This pattern is clear for the period with Employment Subsidies, but less clear for the period with New Start Jobs. For New Starts Jobs we instead see that they have a clear positive effect on firms' survival rates. Overall, our results suggest that targeted employment subsidies can have large positive effects on post-match outcomes of the hiring firms.
Keywords: J08; J20; J60; 330; wage subsidies; labor demand; firms performance